Cost and complexity research of software development to solve the problem of inventory management - Zarudniev, Maksym Andriiovych; Huzhva, Viktor Oleksiiovych (НТУ "ХПИ", 2018)
The article describes the process of estimating the cost and complexity of software development for the task of inventory management of a commercial enterprise to improve the decision-making process at the stage of formation of requirements for similar software products. There are different approaches to inventory management of a commercial enterprise. The algorithms implemented in the system are based on the constraint theory tool –dynamic inventory buffer management. Inventory management according to the theory of restrictions allows to provide a high level of availability of goods with minimal inventory in the system. After analyzing the subject area of inventory management and the methodology of dynamic inventory buffer management, a list of functional and non-functional software requirements was formed, and a data model was designed. The information obtained was used to compile a list of logical files and transactions specific to a particular requirement. From the resulting list of files and transactions, it is determined which elementary data, elementary records and links to files they consist of. The information obtained was used to estimate the size of the software at non-aligned functional points. To take into account the impact of non-functional requirements on the complexity of software development, the VAF alignment factor was calculated, for which it is necessary to give a qualitative assessment of the impact of system-wide requirements on the complexity of the software. The estimation of the complexity of the development was obtained using the COCOMO II methodology, namely, using seven multipliers of the complexity for the case of the initial assessment at the stage of approval of requirements. The calculations were obtained for teams with different professional level and equipment, in the conditions of a significant tightening of the development process, a high level of certainty of risks, without a rigid schedule of work. The cost of development was calculated for several common programming languages: J2EE, C#, C++.

В статье описывается процесс оценки стоимости и трудоемкости разработки программного обеспечения задачи управления запасами торгового предприятия для улучшения процесса принятия решений на этапе формирования требований к аналогичным программным продуктам. Существуют различные подходы к управлению запасами торгового предприятия. Алгоритмы, реализованные в системе основаны на инструменте теории ограничений – динамическом управлении буфером запасов. Управление запасами по теории ограничений позволяет обеспечить высокий уровень наличия товара при минимальных запасах в системе. Проанализировав предметную область управления запасами и методологию динамического управления буфером товарных запасов был сформирован список функциональных и нефункциональных требований к программного обеспечения, а также спроектирована модель данных. Полученная информация была использована для составления перечня логических файлов и транзакций, характерных для конкретного требования. Из полученного списка файлов и транзакций определено, из каких элементарных данных, элементарных записей и ссылок на файлы они состоят. Полученная информация была использована для оценки размера программного обеспечения в не выровненных функциональных точках. Для учета влияния нефункциональных требований на трудоемкость разработки программного обеспечения был посчитан фактор выравнивания VAF, для чего необходимо дать качественную оценку влияния общесистемных требований на трудоемкость программного обеспечения. Оценка трудоемкости разработки была получена с использованием методологии COCOMO II, а именно с использованием семи множителей трудоемкости для случая первичной оценки на этапе утверждения требований. Расчеты были получены для команд с разным профессиональным уровнем и оборудованием, в условиях значительного ужесточения процесса разработки, высоким уровнем определенности рисков, без жесткого графика работ. Стоимость разработки была рассчитана для нескольких распространенных языков программирования: J2EE, C#, C++.
Исследование стоимости и трудоёмкости разработки программного обеспечения для решения задачи управления запасами предприятия
Keywords: software; evaluation methods; COCOMO II method; task of managing vending; методы оценки; метод COCOMO II; торговые запасы; спрос